The impact of corporate governance and moderating effect of firm performance on CSR expenditure of firms in India / Pritpal Singh Bhullar, Pradeep Kumar Gupta and Kiranmai J - Bhullar, Pritpal Singh; Gupta, Pradeep Kumar; J, Kiranmai (UiTM Press, 2024)
This study's primary objective is to examine corporate governance's influence on the allocation of corporate social responsibility (CSR) funds by companies operating in three distinct economic sectors in India, namely fast-moving consumer goods, information technology, and automobiles. The study additionally examines the moderating effect of firm performance on the connection between corporate governance (CG) and corporate social responsibility (CSR) expenditure. Agency theory and resource dependence theory are the basis of this study. Data were collected from the top ten firms in each sector based on their market capitalization from 2014 to 2023. The pooled ordinary least squares (OLS) regression was employed to test the proposed hypotheses. The findings demonstrate a positive impact of corporate governance on corporate social responsibility (CSR) expenditure. Upon examining the moderating effect of firm performance on corporate social responsibility (CSR) expenditure, both proxies of firm performance, Tobin Q and return on equity (ROE), enhance the impact of corporate governance on corporate social responsibility (CSR) spending.